Smartphones, Social Media, and the Role of the Teacher: Impacts on Learning, Mental Health, and the Fight Against Scientific Misinformation - Heslley Machado Silva (Journal of Pedagogical and Teacher Professional Development, 2025)
This article examines the impacts of excessive smartphone and social media use in the school environment, highlighting their cognitive, emotional, and social effects, as well as their role in the dissemination of scientific misinformation. It discusses the need to balance the pedagogical use of these technologies with strategies to minimize distractions and combat the spread of fake news, particularly regarding vaccines and climate change. Additionally, it underscores the essential role of teachers in mediating this scenario, emphasizing the importance of continuous teacher training to develop students' media literacy and critical thinking. The study proposes guidelines and practices for a more conscious use of digital devices in education, contributing to a more critical and productive learning environment